Thine ears shall bleed [videorecording (DVD)] - Bigelow, William; Kouf, Jim; Bigelow, Ben; Zawada, Lea; Near-Verbrugghe, Lucas; Cabell, Hannah (Trinity Creative Partnership, LLC, 2025)
In the 1860s American West, a minister and his family journey across the rugged landscape in their covered wagon. One evening they hear a mysterious sound echoing from the woods, which they believe to be a divine calling. Filled with reverence and convinced they have encountered a manifestation of God, they stop to worship it. As they continue to listen, the tone of the sound shifts, revealing a much darker and more sinister presence lurking in the shadows.